Structural interpretation of Mae Suai Basin, Chiang Rai Province, based on gravity data analysis and modelling - Suebchat Kanthiya (2019)
© 2019 The Mae Suai Basin, an intermountain basin in northern Thailand, became an area of interest in 2014 following the M6.1 earthquake that reactivated the ENE-WSW trending Mae Loa Fault. This fault is associated with the Cenozoic rifting. Terrestrial gravity modelling is a suitable method to visualize subsurface geometry and understand its structural control related to the recent earthquakes. Six hundred twenty-seven terrestrial gravity stations with a spacing of ∼500 m were collected; standard gravity correction methods were applied with a density reduction of 2.67 g/cm 3 to produce the residual Complete Bouguer anomaly (CBA). The residual CBA map reveals a NNE-SSW striking basin, showing gravity lows are located within the basin. The gravity highs cover regions of Triassic granite intrusions to the west and Silurian-Devonian metasedimentary and Carboniferous sedimentary basements to the east. Structural edge detections and basin depth estimates indicate the main fault lineaments lie ENE-SWS and NNE-SSW striking along the eastern and northern margins respectively. These faults may act as splay faults of the active sinistral Mae Loa fault. The gravity models suggest that the Mae Suai Basin is an asymmetrical half-graben with a maximum depth of ∼770 m and a range of basin sediments from 1.9 to 2.3 g/cm 3 . The depocentre is located near the eastern boundary faults. The structural patterns present the rifting has formed within an extensional transfer zone that relates to a releasing bend fault in NNE-SSW trend, linked by the sinistral Mae Loa Fault in NE-SW trend. The E-W maximum of extension in the transfer zone is formed under the activation of the major Cenozoic strike-slip faults in Northern Thailand.